2010
DOI: 10.1093/mp/ssq046
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptional Profiling and Preliminary Study on Heterosis Mechanism of Super-Hybrid Rice

Abstract: Heterosis is a biological phenomenon whereby the offspring from two parents show improved and superior performance than either inbred parental lines. Hybrid rice is one of the most successful apotheoses in crops utilizing heterosis. Transcriptional profiling of F1 super-hybrid rice Liangyou-2186 and its parents by serial analysis of gene expression (SAGE) revealed 1183 differentially expressed genes (DGs), among which DGs were found significantly enriched in pathways such as photosynthesis and carbon-fixation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
100
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 69 publications
(98 reference statements)
12
100
1
1
Order By: Relevance
“…Previous studies of heterosis have revealed possible mechanisms to account for the increased vigor, but the mechanisms that underlie this complex phenotype are still poorly understood, and the role of DNA methylation in heterosis is unclear (26)(27)(28)(29). Our results suggest that the majority of gene-expression changes in hybrids are not associated with cis-acting DNA methylation changes, and instead indicate that trans effects may mediate the majority of the transcriptional differences in hybrid offspring.…”
Section: Resultsmentioning
confidence: 58%
“…Previous studies of heterosis have revealed possible mechanisms to account for the increased vigor, but the mechanisms that underlie this complex phenotype are still poorly understood, and the role of DNA methylation in heterosis is unclear (26)(27)(28)(29). Our results suggest that the majority of gene-expression changes in hybrids are not associated with cis-acting DNA methylation changes, and instead indicate that trans effects may mediate the majority of the transcriptional differences in hybrid offspring.…”
Section: Resultsmentioning
confidence: 58%
“…Notably, the association of increased biomass with CCA1 repression during the day has been independently demonstrated in Arabidopsis intraspecific hybrids (Miller et al, 2012;Shen et al, 2012). In superhybrid rice (Oryza sativa), yield-related quantitative trait loci are also associated with gene expression changes in the circadian clock and light signaling pathways (Song et al, 2010). Moreover, downregulation of CCA1 expression during the day in Arabidopsis diploids leads to more starch at dusk and increased biomass, a phenotype similar to that seen in the hybrids (Ni et al, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…The difference in expression of genes encoding PHYA and PHYB (Si033984, Si033968) between the hybrid and female was not significant. However, no DEG encoding any phytochromes was found in a study by Song et al (2010), although circadian clock genes were also downregulated in hybrid rice. This indicates that the causes of differential expression of circadian clock genes are complex.…”
Section: Discussionmentioning
confidence: 84%
“…Wei et al (2009) investigated transcriptome profiles of superhybrid rice LYP9 and its parental cultivars 93-11and PA64s in 7 tissues and identified 3926 DEGs as a potential group of heterosis-related genes. Song et al (2010) found 1183 DEGs to be significantly enriched in pathways such as photosynthesis and carbon-fixation, and most key genes involved in the carbon-fixation pathway exhibited up-regulated expression in F 1 hybrid rice. Qin et al (2013), provided a repertoire of genes useful for identifying genes involved in maize ear trait heterosis.…”
Section: Introductionmentioning
confidence: 99%